Economic analysis of avocado production systems: Market failures and policy distortions - Ana Luisa Velázquez-Torres; Francisco Ernesto Martínez-Castañeda; Nathaniel Alec Rogers-Montoya; Nicolás Callejas-Juárez; Elein Hernandez (PLoS ONE, 2025)
This study aimed to evaluate competitiveness and profitability at private and social prices, and assess the impact of policies and market failures on avocado production in the State of Mexico. Data were collected from 11 high-density plantations with mature trees between January and July 2021. Three groups were formed, and the Policy Analysis Matrix revealed that all Avocado Production Units (APUs) were profitable at private prices. APU 3 remained competitive when land costs were included, but none of the APUs were profitable at social prices. Indirect subsidies stabilized avocado prices, with producer subsidy rates of 3.09, 2.94, and 3.42 for APUs 1, 2, and 3, respectively. Avocado production showed a comparative advantage due to production-factor failures. As a protected product on the public agenda, avocado has high production costs.